Exploring Nursing Students’ Experiences on Faculty Caring Behaviors in Learning - Tambunan, Evelyn Hemme; Kristiana, Dewi (Jurnal Keperawatan Soedirman, 2022)
Caring behaviors of faculty is one of the most important and influential factors for effective learning. If left only as an assumption of caring, this behavior will not become alive in nursing professional practice. This present study aimed to explore nursing students’ experiences of nursing faculty’s caring behaviors in learning. Descriptive phenomenology was used to collect data from ten senior bachelor nursing students at the private university in Bandung, Indonesia. Data were collected through in-depth interviews and ethical considerations were followed. The result was transcribed and analyzed by using a qualitative content analysis approach. Trustworthiness was established by Lincoln and Guba’s criteria. Nell Noddings’ three great means of nurturing the ethical ideal were reflected in these subjects. The interview data analysis revealed three key themes reflected by all participants: tangible virtue, challenging interaction, and modeling. The six sub-themes emerged reflected as: moral attitude, moral action, supportive interaction, disruptive interaction, personal model and professional model. Results suggested that faculty caring behavior is a useful strategy for nursing students caring behavior development during the program before they enter their real professional role. The exact levels of faculty caring behavior needs to be measured to depict the faculty caring behavior in nursing education.